The Inframerah untuk Kesembuhan Investigasi Terapi Terhadap Penyembuhan Luka Insisi dalam Konteks Ilmu Kesehatan - Rianti, Emilia Devi Dwi; Simamora, Dorta; Ama, Fuad (BIOSAPPHIRE: Jurnal Biologi dan Diversitas, 2024)
Currently, alternative therapies are widely used with the aim of reducing pain, swelling and increasing blood circulation. Infrared rays are used in research as a therapy for healing incisional wounds because infrared can penetrate cells or tissue more deeply. Infrared rays in research as a therapy for healing incisional wounds. The experimental animal samples were 24 male Wistar rats treated with K (-) without infrared therapy, P1 was given infrared exposure at a distance of 24 cm and for 20 minutes. P2 was given infrared exposure at a distance of 16 cm and a time of 20 minutes and P3 was given infrared exposure at a distance of 7 cm and a time of 20 minutes. The results showed that the 12th day change in wound healing occurred in the control group = 0.1 cm; P1= 0.2 cm; P2 = 0.4 cm and P3 = 0.5 cm. The conclusion of the research was that effective infrared therapy was shown in treatment group 1 (P1) with an exposure distance of ± 24 cm, because infrared radiation entered the subcutaneous tissue without excessive stimulation or heating